A Flexible Strategy to Fabricate Gradient Plasmonic Nanostructures. Issue 24 (14th August 2018) - Ai, Bin; Larson, Steven; Bradley, Layne; Zhao, Yiping
Abstract: Gradient plasmonic nanostructures are produced by a straightforward and powerful fabrication strategy—deposition on curved nanomask (DCNM), a physical vapor deposition on a curved mask substrate covered with a monolayer of close‐packed nanospheres. The feasibility of the DCNM strategy is demonstrated by producing well‐ordered Ag gradient single/double nanotriangle (NT) arrays with continuously adjustable color, extinction, localized surface plasmon resonance wavelength, and surface enhanced Raman scattering (SERS). The plasmonic property and the structure gradient are controlled by the size of the mask and the curvature of the curved substrate, as well as the deposition configuration. A plasmonic library of the single/double NT arrays is easily established in a single fabrication. The DCNM strategy can in principle produce a wide range of gradient nanostructures and further be used for flexible components in optical devices, tunable plasmonic SERS sensors, as well as high‐throughput screening of nanostructures. Abstract : Gradient plasmonic nanostructures are produced by a straightforward and powerful fabrication strategy—deposition on curved nanomask, a physical vapor deposition on a curved mask substrate covered with a monolayer of close‐packed nanospheres. A plasmonic library of the single/double nanotriangle arrays is thus easily established in a single fabrication.